Grocery on the Go - Inchiem, Nur Azureen; Ahmat, Mardhiyah; Geofry Lousi, Renee Elissa; Hanif, Fauziah; Zaman, Syahfina (2016)
The name of our business that we will be pursuing will be called Grocery on the Go which will be located at Plaza 33 which is at Penampang area, in Kota Kinabalu, Sabah. Our business is in the form of partnership that consist of five members. Each of us has contribute a certain amount of capital as agreed in the agreement. We all have agreed that Nur Azureen binti Inchiem will be the general manager, Mardhiyah Ahmat as the admin manager, Renee Elissa as the marketing manager, while Fauziah Hanif as the operational manager and lastly Syahfina binti Zaman as the financial manager. As the general manager will be responsible to supervise and help to manage all the other individual department and help guide them when needed in matters regarding to the business. Next the administrative manager whereby she will be responsible for planning and arranging the salary and wages of the workers. The operational manager will be fully responsible on the operation of the business and supervising and synchronizing the operation of business. Other than that for the financial manager will be managing the financial matters of the business such as preparing the budget and financial statement as well as controlling the flow of money of the business. Finally the marketing manager will administer to create marketing plan to introduce our business to the market, identifying customer needs and wants so that we can improve our services and identifying competitors, and forecast future market. We, Grocery on the Go saw the opportunity that this business has potential of success in the future.